ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEPATUHAN PEMILIK UMKM DALAM MEMBAYAR PAJAK PENGHASILAN (Studi Kasus atas Wajib Pajak Pemilik UMKM pada KPP Pratama Batu) - Nurkholidah, Ana Tri; Fachriyah, Nurul (Jurnal Ilmiah Mahasiswa FEB, 2016)
This Research has purpose to know influence of the educational level, taxation of informations services, implementation of tax penalties, and the understanding of self assessment system on the level of owners of SMEs taxpayer compliance in paying income tax. Independent variables in this study is the level of education, taxation of informational services, implementation of tax penalties, and the understanding of self assessment system system while the dependent variable is the owners of SMEs taxpayer compliance. The data of this study were taken from primary data through questionnaires. Questionnaires distributed to as many as 270 pieces of owners of SMEs taxpayer in the Tax Office Primary Batu and questionnaires were processed as many as 86 pieces. The sample were taken by purposive sampling. This study used logistic regression analysis to analyze the variables. The result showed that the level of education, taxation of information services, and implementation of sanctions taxation do not affect the owners of SMEs taxpayer compliance, while the understanding of self assessment system affect the owners of SMEs taxpayer compliance. Â  Keywords: educational level, tax information service, implementation of sanctions taxation, understanding the self assessment system, owners of SMEs taxpayer compliance